Non-performing loans - new risks and policies? NPL resolution after COVID-19: Main differences to previous crises - Johannes Kasinger; Jan Pieter Krahnen; Steven Ongena; Loriana Pelizzon; Maik Schmeling; Mark Wahrenburg (Leibniz Institute for Financial Research SAFE, 2021)
This paper discusses policy implications of a potentialsurge in NPLs due to COVID-19. The study provides an empirical assessment of potential scenarios and draws lessons from previous crises for effective NPL treatment. The paper highlights the importance of early and realistic assessment of loan lossesto avoid adverse incentives for banks. Secondary loan markets would help in this process and further facilitate bank resolution as laid down in the BRRD, which should be uphold even in extreme scenarios. This paper was prepared by the Economic Governance Support Unit (EGOV) at the request of the Committee on Economic and Monetary Affairs (ECON).
Keywords: 330; Covid-19; Non-performing Loans; Bank Resolution; Secondary Loan Markets; BRRD